Sikhism in Malaysia: Negotiating Tradition, Identity and Belonging in a Muslim-Majority Country - Charanjit Kaur; Ashwinder Kaur; Parveenpal Kaur (SUARGA: Studi Keberagamaan dan Keberagaman, 2026)
This paper explores how the Sikh community in Malaysia navigates its religious identity, cultural traditions and sense of belonging within a Muslim-majority society. Drawing upon sociological perspectives, the study examines the lived experiences of Malaysian Sikhs as they balance historical continuity, religious observance and contemporary pressures of integration. Through a combination of historical reflection and qualitative insights, it highlights how Sikh individuals and institutions engage in dynamic negotiations by retaining core traditions such as the turban, the gurdwara and Panjabi language while also adapting to national expectations, educational systems and multicultural policies. These negotiations are situated within broader frameworks of diaspora identity, minority religious experience in plural societies and cultural resilience, with particular attention to generational shifts in identity expression. By analyzing the strategies Sikhs employ to maintain distinctiveness while fostering national belonging, this paper contributes to the broader discourse on religious minorities in Southeast Asia and the evolving meaning of multicultural citizenship in Malaysia.